Obszary, obiekty i urządzenia ważne dla bezpieczeństwa państwa – propozycja modyfikacji systemu obowiązkowej ochrony w zakresie podmiotu wykonującego czynności ochronne .......... 163 - Bogdalski, Piotr (Systemy bezpieczeństwa: Wymiar lokalny i państwowy, 2020)
The Act of 22 August 1997 on the Protection of Persons and Property introduced a system of statutory, obligatory protection of areas, objects and equipment that are important for state interests. The introductory part of the article presents the general characteristics of this system, in particular – the subject of protection, categories of important state interests determining the granting of protection, the process of identification of property subject to protection, the entity obliged to ensure protection and the entities through which protection is implemented. In the further part of the article, the functioning of private armed security companies is critically evaluated. In this respect, reference is made to opinions expressed in the environment of persons related to the system of property protection, as well as research findings relating to the private security market. In the opinion of the author of the article, entrusting private security companies with the protection of areas, facilities or equipment important for public security and state defence raises significant doubts. Consequently, the final part of the article contains a discussion on the change of the current system of protection and indicates the exemplary possibilities of its modification.